Reaching the “Last Mile”: describing community clinics implemented to increase COVID-19 vaccine uptake in Peel region, Canada - Jannice So; Dannielle Nicholson-Baker; Subrana Rahman; Nancy Ramuscak; Anthony Reid; Monali Varia; Nazia Peer; Elizabeth Estey Noad; Sondra Davis; Shaza A. Fadel; Erica Di Ruggiero (BMC Public Health)
Abstract Background COVID-19 hit Canada hard and exacerbated health inequities, notably among ethnoracially minoritized populations. By August 2021, some areas in Peel region (Ontario, Canada) continued to have high COVID-19 infection rates and low COVID-19 vaccine coverage. To increase first dose uptake, Peel Public Health implemented smaller community-based vaccination clinics in addition to pre-existing mass vaccination (fixed) clinics. This study describes these community clinics and those who received their first dose at a community clinic to determine whether local public health efforts to implement community clinics reached different population groups and whether these community clinics contributed to an increase in uptake of the first dose of COVID-19 vaccines. Methods We conducted a descriptive, cross-sectional study using data from the Ontario COVID-19 vaccination registry (COVaxON). We included eligible Peel residents 12 years and older who received a COVID-19 vaccine within community and fixed clinics between September 2021 and August 2022. Clinics were classified based on clinic type (community/fixed), and location. COVID-19 vaccine uptake for smaller geographic areas designated by postal codes was calculated at the beginning and end of the study period. Clinic and attendee characteristics were analyzed using descriptive statistics. Results There were 177 community and 11 fixed clinic sites that operated during the study period. Community clinics administered 98,965 doses (27%) of COVID-19 vaccine and fixed clinics administered 264,021 doses (73%). A slightly higher proportion of first doses were administered in community clinics (8.1%) compared to fixed clinics (7.9%) and community clinics saw a higher proportion of first dose recipients from low-coverage areas (23% versus 19% in fixed clinics). Clinics in faith-based organizations, schools and shopping areas administered the most doses among community clinic locations. The absolute increase in first dose vaccine uptake was 11% over the study period. Conclusions Almost 100,000 doses of COVID-19 vaccine were administered in community clinics, which contributed to increased overall vaccine coverage in Peel region. A slightly higher proportion of first doses were administered in community clinics compared to fixed clinics and a higher proportion of doses to residents of low-coverage areas.